Cardio-facio-cutaneous syndrome: Does genotype predict phenotype? - Allanson, Judith E (2011)
Cardio-facio-cutaneous syndrome is a sporadic multiple congenital anomalies/mental retardation condition principally caused by mutations in BRAF, MEK1, and MEK2. Mutations in KRAS and SHOC2 lead to a phenotype with overlapping features. In approximately 10–30% of individuals with a clinical diagnosis of cardio-facio-cutaneous, a mutation in one of these causative genes is not found. Cardinal features of cardio-facio-cutaneous include congenital heart defects, a characteristic facial appearance, and ectodermal abnormalities. Additional features include failure to thrive with severe feeding problems, moderate to severe intellectual disability and short stature with relative macrocephaly. First described in 1986, more than 100 affected individuals are reported. Following the discovery of the causative genes, more information has emerged on the breadth of clinical features. Little, however, has been published on genotype-phenotype correlations. This clinical study of 186 children and young adults with mutation-proven cardio-facio-cutaneous syndrome is the largest reported to date. BRAF mutations are documented in 140 individuals (~75%), while 46 (~25%) have a mutation in MEK 1 or MEK 2. The age range is 6 months to 32 years, the oldest individual being a female from the original report [Reynolds et al., 1986]. While some clinical data on 136 are in the literature, fifty are not previously published. We provide new details of the breadth of phenotype and discuss the frequency of particular features in each genotypic group. Pulmonary stenosis is the only anomaly that demonstrates a statistically significant genotype-phenotype correlation, being more common in individuals with a BRAF mutation.